A rare diagnosis of abdominal pain presentation in the emergency department: Idiopathic omental bleeding. Issue 51 (December 2017) - Wu, Yen-Hung; Liu, Kuan-Ting; Wen, Chun-Kai
Abstract: Rationale: Idiopathic omental bleeding is a rare cause of acute abdomen, with only a few reported cases. It usually presents with abdominal pain and may be life-threatening. As it rarely occurs, it may not be considered initially during patient presentation. Patient concerns: A 35-year-old male came to our emergency department with abdominal pain present for around 5 to 6 hours. The patient complained of left upper quadrant abdominal pain after eating breakfast. The only associated symptom was 3 episodes of vomiting up food. Physical examination revealed mild left upper quadrant abdominal tenderness without muscle guarding or rebounding pain. Blood examination showed leukocytosis with neutrophil predominance and C reactive protein elevation. The pain was persistent and relief was not obtained by medication. Diagnoses: Computed tomography showed a large lobular-contour homogenous slightly hyperdense lesion without enhancement along the greater curvature of the stomach in the lesser sac. A surgeon was consulted and laparotomy was suggested. Hematoma was found at Morrison pouch, subsplenic fossa, and lesser sac under operation. Intervention: Laparotomy and ligation for hemostasis. Outcomes: The patient was discharged with stable condition after 7 days of hospitalization. Lessons: This diagnosis should be considered in patients presenting with epigastric pain and vomiting after eating while in the emergency department because this disease might be life-threatening. This case highlights 2 important learning points. First, idiopathic omental bleeding could occur after eating in patients without underlying disease or trauma history, and this disease should be taken into consideration when acute abdomen occurs. Second, emergent laparotomy is indicated if the cause of acute abdomen is not clear.